Ratas nascidas com restrição de crescimento intrauterino submetidas à natação antes e durante a prenhez: repercussões maternas e perinatais - Corvino, Silvana Barroso [UNESP] (2015)
To evaluate the swimming effect before and during pregnancy of rats born with intrauterine growth restriction (IUGR) and on their offspring. For this, IUGR rat offspring were obtained from the streptozotocin-induced severely diabetic (SD) dams. The nondiabetic and SD pregnant rats generated offspring with appropriate (Control, C) and small (IUGR) weight for pregnancy age, respectively. At adult life, C and IUGR groups were distributed into four subgroups: non-exercised control (C): exercised control (Cex), non-exercised IUGR (IUGR) and exercised IUGR (IUGRex). The rate of mated IUGR rats was reduced compared to control group. The IUGR rats presented decreased body weight from birth to lactation regardless of physical exercise. At day 90 of life, IUGR rats presented glucose intolerance compared to C group. The maternal heart, pancreas and lung weights were increased, and the adipose tissues (pancreatic, peritoneal, esternal and periovarian fat), total and relative adiposity of IUGRex rats were reduced compared to Cex. In the offspring, female and male body weights were reduced in the IUGR and IUGRex groups in relation to those of C and Cex, respectively. There was increase of the newborn classified as appropriate for pregnancy age in IUGRex group. The relative weights of heart of male offspring and of brain and lung of female and male offspring were increased in the IUGEex group than Cex. Thus, the swimming applied before and during rat pregnancy prevented glucose intolerance, reduced general adiposity and increased maternal and offspring's organ weight, showing benefit effect of physical exercise for IUGR rats